2005
DOI: 10.1002/cbic.200400174
|View full text |Cite
|
Sign up to set email alerts
|

Transport Of Surface‐Modified Nanoparticles Through Cell Monolayers

Abstract: We synthesized three peptides, a D-polyarginyl peptide (r8(FITC)), a Tat peptide (Tat(FITC)), and a control peptide (Cp(FITC)) and attached each to amino-CLIO, a nanoparticle 30 nm in diameter. We then examined the effective permeability, Peff, of all six materials through CaCo-2 monolayers. The transport of peptide-nanoparticles was characterized by a lag phase (0-8 h) and a steady-state phase (9-27 h). The steady-state Peff values for peptides were in the order r8(FITC)>Tat(FITC)=Cp(FITC). When r8(FITC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 61 publications
1
61
0
1
Order By: Relevance
“…29 Another proposed way in which the membrane can be compromised is the alteration of membrane lipid components. 30 It is, however, difficult to distinguish between the bactericidal activity of nanoparticles from the ions released by the nanoparticles themselves. 31 Previously, Ruparelia et al estimated the concentration of released ions for 10 mg of copper nanoparticles suspended in 100 mL nutrient media and distilled water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Another proposed way in which the membrane can be compromised is the alteration of membrane lipid components. 30 It is, however, difficult to distinguish between the bactericidal activity of nanoparticles from the ions released by the nanoparticles themselves. 31 Previously, Ruparelia et al estimated the concentration of released ions for 10 mg of copper nanoparticles suspended in 100 mL nutrient media and distilled water.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of inhibition of bacterial growth observed in this study was found to be variable and size-dependant. The smallest CuO nanoparticles (particle size 20 ± 1.24 nm) synthesized at the lowest Particle size (nm) Particle size (nm) 30 31…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…In drug delivery application, the critical step is the transport across cell layers (Koch et al, 2005) and the internalization of nanoparticles into specific cells, a process often limited by poor targeting specificity and low internalization efficiency of therapeutic ligands grafted on the nanoparticles. A number of studies have addressed the cell-surface binding or cell uptake of functionalized SPIONs.…”
Section: Discussionmentioning
confidence: 99%
“…Following cellular uptake, AuNPs are stored in endosomal/lysosomal vesicles. In order to liberate these AuNPs and introduce the drug which has been delivered into the cell cytoplasm, the NPs need to be modified by the conjugation of membranetranslocating sequence-based peptides which enable them to traverse monolayers [51] . Tumor necrosis factor-alpha (TNF-α) is a potent, multifunctional cytokine which not only plays a critical role in inflammation and immunity, but also exhibits anticancer properties [52] .…”
Section: Wwwchinapharcom Lim Zzj Et Almentioning
confidence: 99%